(untitled) (Inovasi, 2023)
This paper describes the results of legal synchronization analysis of the Special Regional Regulation Number 3 of 2017 concerning the Maintenance and Development of Culture (Perdais No. 3 of 2017) with Law Number 5 of 2017 concerning the Advancement of Culture (UU Pemajuan Kebudayaan). The analysis is based on the existence of a number of mandates from the Law for the Advancement of Culture to local governments. The existence of regional regulations (perda) of culture is important as the legal basis for cultural policies in the region. Given that theoretically, a regional regulation should not conflict with the regulations that are hierarchically above it, it is important for this regional regulation to be in line with the Law for the Advancement of Culture. To achieve this, a normative legal study was carried out with a synchronization approach to the Perdais Yogyakarta No. 3 of 2017 with the Law for the Advancement of Culture. Based on the synchronization results obtained, it was revealed that systematically the number of chapters in the Perdais Yogyakarta No. 3 of 2017 is more than the Law for the Advancement of Culture, but the number of articles is much less. It has also been described that the Law for the Advancement of Culture has mandated a number of matters to local governments. In this regard, Perdais Yogyakarta No. 3 of 2017 seeks to regulate these mandates in its articles. In this regional regulation, most of the mandates of the Law for the Advancement of Culture to local governments have been regulated by the said regional regulation. This reflects the misalignment of cultural policy concepts between the central and local governments. Keywords: culture, cultural advancement, regional law, cultural polic